SKIN LOAD PERFORMANCE OF DOUBLE-SKIN FACADE IN INDONESIA - Rosady Mulyadi; Gyuyong Yoon; Masaya Okumiya (Journal of Architecture&ENVIRONMENT, 2011)
Models of double-skin facade with various outer and inner glass skin combinations, distances and orientations has been analyzed using numerical simulation. The results show that the thickness of the glass skin is important in reducing solar heat gain: as the thickness of the glass is increased, solar heat gain decreases. On the contrary, as the distance between the glass skins is increased, thermal transmittance becomes lower. Analysis for the condensation found that throughout the building operation time there is no condensation found at the double-skin facade. In comparison to the single-skin façade, double-skin facade is better in reducing skin load.